Assessing the Impact of Contextual Teaching and Learning (CTL) Approach in Reading Instruction: A Multiple Case Study - Samsudin, Samsudin; Weda, Sukardi; Amirullah, Amirullah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research reveals the impact of implementing the Contextual Teaching and Learning (CTL) Approach in the teaching of reading. Through the CTL approach, reading learning is integrated with real-world contexts, making learning more meaningful and relevant to students. This pedagogical framework aims to engage students in deeper understanding and critical thinking while facilitating the application of reading skills in various contexts. However, the effectiveness of CTL in reading instruction has been a subject of debate, with some studies reporting positive results while others show limited effectiveness, especially for students with low vocabulary or intelligence. This study aims to comprehensively assess the impact of CTL on reading learning, considering aspects such as vocabulary improvement, student motivation, reading comprehension, and learning outcomes. Through a qualitative approach and a multiple case study, involving 40 second-semester students from two universities in Sumbawa Island, West Nusa Tenggara Province, this study found that CTL can significantly improve students' psychological, linguistic, and achievement factors. In terms of psychological factors, students showed increased motivation and engagement in reading activities when the material was relevant to their lives and interests. Linguistically, CTL facilitates vocabulary improvement through personalized learning strategies and culturally relevant materials. In addition, CTL had a positive impact on students' achievement in reading, which was reflected in their improved comprehension and scores. These findings suggest that CTL can effectively improve students' reading skills and motivation when implemented with consideration of contextual relevance and personalized learning approaches. However, further research is needed to understand the complex effects of CTL on various aspects of student learning outcomes. Continuous evaluation and refinement of CTL implementation are essential to maximize its effectiveness in improving students' reading skills and their academic achievement.